SP10.2.2 Emergency Management of Incisional Hernia. (9th August 2022) - Omar, Islam; Townsend, Abby; Williams, Catrin; Jones, Annabel; Wilson, Jeremy; Magee, Conor
Abstract: Introduction: Incisional hernia is a common complication after abdominal surgery. Operating on a hostile field renders the management of incisional hernia quite challenging. Presentation with incarcerated or obstructed incisional hernia can further complicate the picture. This study aims to describe the outcomes and burden of emergency management of incisional hernia. Methods: A retrospective study has been conducted. We reported the patients' demographics, primary surgery details, hernia characteristics, and mode of presentation and management. Results: Forty-five patients were included in the analysis. Mean age was 66.78;SD±15.32. Thirty-one (69%) were females. Mean BMI was 35.49;SD±10.46. They had significant comorbidities including diabetes, CKD, COPD, and malignancy; 31.1%, 13.3%, 11.1%, 11.1% respectively. Twenty-two (48.8%) had incisional hernia after midline incision. 25(55.6%) presented with bowel obstruction. Thirty-two had a surgical repair, and ten were managed conservatively. The mean time from admission to surgery was 1.4;SD±2.1. Meshes were used in 10(31.25%) patients. The mean duration of surgery was 114.03;SD±60.55 minutes. Ten patients needed HDU/ITU; 9 of them were managed surgically. Complications rate (CD≥III) was 20%. The 30-day mortality rate was 8.89%. Six (18.75%) patients had recurrence after surgical repair. Thirty patients had CT, 7 had X-rays, and one had US. The mean hospital stay was 8.71;SD±8.8, with an overall hospital stay of 392 days. Fifteen patients were readmitted, and seven came back without staying >24 hours. Conclusion: Emergency presentation of incisional hernia carries a high risk of morbidity and mortality and represents a high burden.